2010
DOI: 10.4103/0974-1208.69337
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on plasma membrane cholesterol efflux and spermatozoal function

Abstract: The process of sperm maturation, capacitation, and fertilization occur in different molecular milieu provided by epididymis and female reproductive tract including oviduct. The different tissue environment with different oxygen tension and temperature may still influence the process of sperm maturation and capacitation. Reactive oxygen species (ROS) is reported to be an initial switch that may activate the molecular process of capacitation. Therefore, the generation of reactive oxygen species and its possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The main results obtained with the functional enrichment analysis of differentially expressed proteins in seminal plasma from subjects presenting low sperm DNA fragmentation were the hyper‐representation of phospholipase activity and lipoprotein particle remodelling and level regulation processes. Studies have shown that these properties, associated with sperm lipid catabolism, are important for sperm energy and capacitation‐associated membrane remodelling to reach its fertilization potential . The proteins involved in these processes, phospholipase A1, phospholipase A2 and lipoprotein lipase were found exclusively in this group, suggesting an involvement of these proteins and proprieties with normal sperm function and their possible association with sperm DNA fragmentation.…”
Section: Discussionmentioning
confidence: 90%
“…The main results obtained with the functional enrichment analysis of differentially expressed proteins in seminal plasma from subjects presenting low sperm DNA fragmentation were the hyper‐representation of phospholipase activity and lipoprotein particle remodelling and level regulation processes. Studies have shown that these properties, associated with sperm lipid catabolism, are important for sperm energy and capacitation‐associated membrane remodelling to reach its fertilization potential . The proteins involved in these processes, phospholipase A1, phospholipase A2 and lipoprotein lipase were found exclusively in this group, suggesting an involvement of these proteins and proprieties with normal sperm function and their possible association with sperm DNA fragmentation.…”
Section: Discussionmentioning
confidence: 90%
“…Cholesterol helps maintain the integrity and fluidity of the sperm membrane, so its influx and efflux could influence sperm membrane function (Sheriff and Ali, ). A functional link between cholesterol binding by HE1/NPC2 and sperm maturation was previously proposed: porcine HE1/NPC2 functions as cholesterol‐specific binding protein during sperm membrane remodeling, improving sperm function by removing cholesterol from sperm membranes (Okamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the most connected node is cholesterol. This molecule plays a key role in pre-and post-ejaculatory life of spermatozoa [Sheriff and Ali 2010;Schwarz et al 2013;Saez et al 2011;Rajasekharan et al 2013]. Indeed, it infers the physical-chemical behavior of male gamete membranes.…”
Section: Node Degreementioning
confidence: 99%